Cell-Based Fish: A Novel Approach to Seafood Production and an Opportunity for Cellular Agriculture - Rubio, Natalie; Datar, Isha; Stachura, David; Kaplan, David; Krueger, Kate (Frontiers in Sustainable Food Systems, 2019)
Cellular agriculture is defined as the production of agricultural products from cell cultures rather than from whole plants or animals. With growing interest in cellular agriculture as a means to address public health, environmental, and animal welfare challenges of animal agriculture, the concept of producing seafood from fish cell- and tissue-cultures is emerging as an approach to address similar challenges with industrial aquaculture systems and marine capture. Cell-based seafood—as opposed to animal-based seafood—can combine developments in biomedical engineering with modern aquaculture techniques. Biomedical engineering developments such as closed-system bioreactor production of land animal cells create a basis for the large scale production of marine animal cells. Aquaculture techniques such as genetic modification and closed system aquaculture have achieved significant gains in production that can pave the way for innovations in cell-based seafood production. Here, we present the current state of innovation relevant to the development of cell-based seafood across multiple species, as well as specific opportunities and challenges that exist for advancing this science. The authors find that the physiological properties of fish cell- and tissue- culture may be uniquely suited to cultivation in vitro. These physiological properties, including tolerance to hypoxia, high buffering capacity, and low-temperature growth conditions, make marine cell culture an attractive opportunity for scaled production of cell-based seafood; perhaps even more so than mammalian and avian cell cultures for cell-based meats. This opportunity, coupled with the unique capabilities of crustacean tissue-friendly scaffolding such as chitosan, a common seafood waste product and mushroom derivative, presents promise for cell-based seafood production via bioreactor cultivation. To become fully realized, cell-based seafood research will require more understanding of fish muscle cell and tissue cultivation; more investigation into serum-free media formulations optimized for fish cell culture; and bioreactor designs tuned to the needs of fish cells for large scale production.